Efeito no ensino de duas e quatro relações condicionais auditivo-visuais na emergência do tato em pessoas com transtorno do espectro autista - Nogueira, Renato Amdei (Universidade Federal de São Carlos, 2025)
The field of clinical practice has applied strategies for teaching naming repertoires to individuals with Autism Spectrum Disorder (ASD), but there is still a gap regarding the emergence of tact resulting from the teaching of auditory-visual conditional relations with two or four comparison stimuli. Thus, the objective of this study was to investigate the acquisition of emergent tact relations derived from two teaching procedures, one with two and the other with four comparison stimuli. To this end, an experimental study was conducted using an alternating treatment design combined with a non-concurrent multiple baseline design across participants, with a translational approach. Two children diagnosed with ASD, aged seven and eight years, participated in the study. Two listener-teaching procedures were conducted in a semi-alternated manner: one with two comparison stimuli (2C) and another with four (4C), followed by tact probes. In the 2C procedure, both participants reached the learning criterion in fewer trials. One participant demonstrated tact emergence only for the stimuli from the 4C procedure, while the other showed tact emergence for the stimuli from the 2C procedure and for three stimuli from the 4C procedure. The results suggest that teaching auditory-visual conditional relations can generate the emergence of tact in individuals with ASD with both two and four comparisons.
Effect of teaching two and four auditory-visual conditional relations on the emergence of tacting in individuals with autism spectrum disorder
Keywords: Emergência de tato; Relações condicionais; Análise do comportamento; Transtorno do Espectro Autista; Tact emergence; Conditional relations; Behavior analysis; Autism Spectrum Disorder; CIENCIAS HUMANAS::PSICOLOGIA